A real-world study of hereditary angioedema patients due to C1 inhibitor deficiency treated with danazol in the Brazilian Public Health System - Ritter, Alessandra Mileni Versuti; Silva, Suelen; de Paula, Robson; Senra, Juliana; Carvalho, Fabio; Ribeiro, Tatiane; Valle, Solange Oliveira Rodrigues (Frontiers in Medicine, 2024)
Hereditary angioedema (HAE) due to C1 inhibitor (C1-INH) deficiency is an ultra-rare autosomal dominant inherited disease that affects 1 in 67,000 people in the world. The attacks are based on subcutaneous and submucosal edema that can lead to death if not properly managed. Considering the lack of information on clinical management of Brazilian patients with HAE, the aim of this study was to identify and characterize patients with HAE-C1-INH that used danazol prophylactic treatment in the Brazilian public health system (SUS) and the health care resources utilization (HCRU). Methods: This was an observational retrospective database study with patients treated with danazol from January 2011 until December 2021 within the SUS. The HAE cohort included patients with 12 years or older with at least one record for ICD-10 D84.1, one claim for danazol record and at least 6 months of available history in the database. Results: Our study included 799 patients treated in the SUS, with mean (SD) age at danazol initiation of 40 years ( 16). The number of patients with HAE showed a similar distribution over this 10 years period analyzed with the highest number of patients in 2015 (n=509) and 2016 (n=480). 253 (32%) patients had record of at least one attack. Of those, 45 (17.8%) had at least one procedure HAE-related hospital admission and 128 (50.6%) had at least one HAE-related hospital admission. The mean (SD) hospitalization length of stay was 5 (8) days. Over 14% (n=36) of HAE patients with attack (n=253) had at least one HAE-related ICU admission. Conclusion: This database study is the strategy used to allow us to find and describe the characteristics of patients with HAE who use danazol for long-term prophylaxis in the SUS and identify HCRU outcomes of interest such as hospitalizations, inpatient and outpatient settings. The high rate of attacks, hospitalization and general resources uses highlights the necessity to increase awareness of new strategies and accurate approach to treat HAE patients. Therefore, our findings are important indicators that our health system and guidelines need to be revised and improved to properly diagnose, treat, and assist patients with HAE.